The Art and Science of Military Deception. - Rothstein, Hy (Artech House, 2013)
It is said that deception among people in a civilized society is something to be loathed even though it seems to be part of human nature; but deception in war is a virtue. Properly designed and executed, stratagems reduce the horrific costs of war. This book is a comprehensive collection of classic articles on deception, hand-picked and expertly introduced by well-known experts on military deception. The purpose of this book is to set in motion a renaissance for using deception as an instrument of statecraft. The various sections are designed to cumulatively provide sufficient breadth and depth.